Dimensions of Postwar Philippine Economic Progress - Williamson, Jeffrey G. (Quarterly Journal of Economics, 1969)
I. Introduction, 93. — II. Economic growth in the Philippines: the initial reconnaissance, 95. — III. Education as a source of PhiHppine growth, 99. — IV. An hypothesis and a comparative evaluation: Asia and Latin America, 105. — V. Summary, 108.